A content analysis of the media coverage of the 2014 presidential elections in Egypt: the case studies of CBC and Channel 1 - Barsoum, Jiana (AUC Knowledge Fountain, 2015)
Television broadcasting offers a platform for bringing the attention to issues of high importance, and forming opinions on these issues. With a high dependency on television broadcasting in Egypt to receive news and information about current events to formulate opinions, regulated television broadcasting is very crucial to aid the shift towards a more democratic nation. Balanced and impartial reporting is essential to ensure pluralism in the information presented. Hence, this thesis examines the performance of public media compared to privately owned media in light of their coverage of the 2014 presidential elections. The overall theoretical approach is based on Article 19 and UNESCO's standard guidelines for broadcasting during election times. CBC and Channel1 are used as case studies from both media sectors. Qualitative content analysis is used to analyze coverage under both channels, from 3rd May to 23rd May 2014 (the official campaigning period), to mainly assess for balance, fairness, impartiality and comprehensiveness. Current affairs talk shows, as well as news content were covered, on the basis of popularity and relevance to the elections. Furthermore, the research examines policy changes that can be undertaken to ensure better regulation of the coverage of information during election times.